Quality and university teaching: some criteria for its evaluation (2020)
In this document, a reflection is made on the assessment of the quality of teaching in higher education. The work starts from the review of articles and documents from the Colombian context, related to the concept of quality applied to universities. Then, an interpretation of quality teaching is proposed in the light of the new professional performance scenarios, where the teacher ceases to be a player of knowledge to become a learning advisor. In this sense, it was established that the teaching work is made up of three dimensions, namely: disciplinary, pedagogical and human, each one composed of different characteristics, through which the quality of the university teaching practice can be assessed. It is concluded that it is possible to establish tangible criteria to objectively determine the quality of teaching, which should be incorporated into the models that guide the accreditation processes of higher education institutions.